Analisis Kualitas Pendidik dan Tenaga Kependidikan dalam Upaya Meningkatkan Mutu Pendidikan di SMAN 1 Krembung - Boy Eka Saputra; Ahmad Dimas Nur Fauzi; Agustina Hanivia Cindy; Windasari, Windasari (Yayasan Literasi Sains Indonesia, 2024)
Excellent education quality is an important cornerstone in efforts to strengthen the competitiveness of a society. One of the most crucial elements in achieving this is the quality of educators and support staff in educational institutions. A study was conducted to examine this aspect in depth, focusing on the situation at SMAN 1 Krembung. The method used was a qualitative approach through literature analyses. Overall, the quality of educators and support staff at SMAN 1 Krembung can be said to be satisfactory. However, there are still challenges that need to be overcome. Therefore, it is important for them to continue to attend training and development programs organized by related parties. To face these challenges, close cooperation between the school and related agencies, as well as a strong commitment from the educators and support staff to continue learning and improving themselves, is required. Such training and educational development will not only improve their technical skills but also their understanding of educational developments and community needs. With the awareness of the importance of improving the equality of education, SMAN 1 Krembung can continue to progress in providing quality educational services for students. This not only benefits the individuals involved, but also contributes to the development of a competitive society at both local and national levels. Therefore, concrete steps need to be taken to ensure that the quality of education at SMAN 1 Krembung continues to improve in line with the times and global demands.